2019
DOI: 10.1002/pbc.28057
|View full text |Cite
|
Sign up to set email alerts
|

The association of mediastinal mass in the formation of thrombi in pediatric patients with non‐lymphoblastic lymphomas

Abstract: BACKGROUND:Children diagnosed with cancer are at a significantly higher risk of developing a thrombotic event (TE) compared to the general population. The rarity of these events makes it difficult to discern the specific risk factors; however, age, sex, presence of central venous lines, inherited thrombophilia and mediastinal mass may play a role. The primary aim of this study is to identify prognostic characteristics of children diagnosed with non-lymphoblastic lymphomas associated with a greater risk of deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 10 publications
5
13
0
1
Order By: Relevance
“…In our study we observed a trend towards reduction in M-TE with primary thromboprophylaxis but was not statistically significant likely related to small cohort size. Furthermore, mediastinal mass associated TE incidence of 8.5%, has been reported with the odds increasing by 2.2 when the SVC was >25% compressed [8]. This is akin to our incidence of 9.2% with observed increase in SVC compression with M-TEs versus those without.…”
Section: Discussionsupporting
confidence: 79%
“…In our study we observed a trend towards reduction in M-TE with primary thromboprophylaxis but was not statistically significant likely related to small cohort size. Furthermore, mediastinal mass associated TE incidence of 8.5%, has been reported with the odds increasing by 2.2 when the SVC was >25% compressed [8]. This is akin to our incidence of 9.2% with observed increase in SVC compression with M-TEs versus those without.…”
Section: Discussionsupporting
confidence: 79%
“…Since the risk of some complications might be higher during treatment (i.e., intensive use of CVC), the IRs per 1000 CVC-treatment days were also calculated, which still showed that the insertion of a SL PICC is associated with a significantly higher risk of (severe) complications and local infections in particular compared to a TIVAP. The high rate of complications associated with PICCs was also reported previously in adult patients with HL and pediatric oncology patients in general [1,[9][10][11][12][13]. Three studies did investigate risk factors for CVT (CVC and non-CVCrelated) specifically in pediatric patients with lymphoma.…”
Section: Discussionsupporting
confidence: 55%
“…However, general anesthesia is needed for insertion, sedation for removal, percutaneous punctures to access the port, and a larger scar will remain visible after removal, whereas these disadvantages do not apply to PICCs. On the other hand, higher incidence rates of mechanical failure, CVC-related infections, and CVC-related central venous thrombosis (CVT) have been associated with PICCs when compared to other CVC-types in a variety of adult and pediatric patients (i.e., oncology, intensive care unit, total parenteral nutrition) [1][2][3][4][5][6][7][8][9][10]. However, the incidence of all CVC-related complications for patients with HL specifically has not been described previously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El estudio concluye que los individuos con una masa mediastínica con un 25% o más de grado de compresión de la VCS, tenían más probabilidades de desarrollar eventos trombóticos. Este hallazgo destaca un grupo de niños de alto riesgo que pueden beneficiarse de la anticoagulación profiláctica [28].…”
Section: Epidemiología Y Etiologíaunclassified